Pengaruh Sosialisasi Perpajakan, Penegakan Hukum, dan Sanksi Perpajakan Terhadap Penggelapan Pajak - Shifa Rosmawati; Maman Darmansyah (Yayasan Literasi Ilmiah Indonesia, 2023)
This study aimsaims to examine the effect of taxsocialization, law enforcement, and tax sanctions on tax evasion at the Pratama Tax Office Serpong. The sample in this study usedsimple random sampling method. The population in this study were 49.019 taxpayers registered at KPP Pratama Serpong in 2022. This study uses quantitative methods with associative. The number of samples in this research totalled 100 respondents. Sampling technique used was purposive sampling method with using Slovin Formula. Collecting data using questionnaires and processed using statistical SPSS version 25. Data analysis technique used was multiple linear regression.The results showed that simultaneously taxsocialization, law enforcement, and tax sanctions have an effect ontax evasion. The partial results of the reseach show that tax socialization has a positive effect on tax evasion, law enforcementhas a positive effect on tax evasion, and tax sanctions has a positive effect on tax evasion.